Role of acellular bovine urinary bladder submucosa on skin wound healing in Iraqi goats: Ahmed H. F. AL-Bayati1, Hameed A. K. AL-Tememe1, Nada H. A. AL-Mudallal2 - AL-Bayati, Ahmed H. F. (The Iraqi Journal of Veterinary Medicine, 2016)
This study is designed to assess the effectiveness of bovine urinary bladder submucosa on healing of cutaneous wound in Iraqi goats. A 32 (2X2) cm of full-thickness cutaneous wounds were induced in eight goats, two on each side of the lateral thoracic region. The wounds were divided into two equal groups (16 wounds/ group); treatment group included the wounds on the right side which were treated by covering the wound beds with strips of acellular sterilized bovine urinary bladder matrix. While, the wounds on the left side were left without any treatment (control group). The results were evaluated clinically (along) and histopathologically on 7, 14, 21, and 35 days post-inducing of wounds. The clinical evaluation of treated wounds showed that the wound healing process contraction%, re-epithelization % and total wound healing % were P<0.05 significantly than that of control wounds at 35 days of the study. The histopathological results confirmed that urinary bladder matrix treated wounds have enhanced cellularity, increased vasculature, thick and large granulation tissue suggesting enhanced cutaneous healing, than those in untreated wounds. Depending on the clinical and histopathological findings, this study concluded that a cellular bovine urinary bladder matrix play an important role in stimulation of cutaneous wound healing of goats without signs of immuno-rejection.